Unilateral Tax Policy in the Open Economy - Miriam Kohl; Philipp Richter (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper examines the effects of unilateral tax policy in the open economy. We construct a general equilibrium trade model with heterogeneous agents allowing for country asymmetries. We find that in contrast to a symmetric country set-up the share of exporting firms is endogenous. We show that a unilateral increase in the tax rate affects the factor allocation in the regulating country and the trading partner country differently. We further derive the implications for aggregate income and inequality in both countries.
Keywords: F12; 330; International trade; Income inequality; Redistribution; Heterogeneous firms